Self-Assessment on Digital Pedagogy of Indonesian Gen Z Student-Teachers - Safira Afifah Sabrina; Jamil Suprihatiningrum (Universitas Negeri Medan, 2026)
The rapid advancement of digital technology requires pre-service teachers to possess strong digital pedagogical skills to design and implement effective learning in the digital era. This study aimed to analyze the digital pedagogy skills of Generation Z pre-service chemistry teachers and examine differences based on gender and the number of software applications used. A survey method was employed involving 158 pre-service chemistry teachers from seven State Islamic Universities in Indonesia. Data were collected using a five-point Likert-scale questionnaire covering three dimensions: pedagogical orientation, pedagogical practices, and digital pedagogical competencies. The data were analyzed descriptively and using an independent samples t-test and one-way ANOVA. The findings showed that the respondents’ digital pedagogy skills were generally in the good category, with pedagogical orientation obtaining the highest mean score, followed by pedagogical practices and digital pedagogical competencies. No significant differences were found based on gender or the number of software applications used. These results indicate that although Generation Z pre-service chemistry teachers are familiar with digital technology, their ability to integrate technology pedagogically still requires further strengthening through relevant training and practical learning experiences.